Bowie gen. nov., a diverse lineage of ground-dwelling spiders occurring from the Himalayas to Papua New Guinea and northern Australia (Araneae: Ctenidae: Cteninae) - Jäger, Peter (Zootaxa, 2022)
A new genus in the spider family Ctenidae Keyserling, 1877 is described from Asia: Bowie gen. nov. belongs to the subfamily Cteninae and all members formerly described were placed so far in the genus Ctenus Walckenaer, 1805. After morphological as well as preliminary molecular characters were checked, it was clear that a new genus had to be erected to accommodate this predominantly Asian lineage of ground-dwelling spiders. As is the case in most Ctenidae generally, it was not easy to find apomorphic characters diagnosing this new taxon. Therefore, a combination of morphological characters is used to define all congeners. An important and newly introduced character in this respect is –among others– the fused patellar crack of the male palp. Forty-nine valid species are transferred to the new genus (first country/province records of particular species underlined): Bowie martensi (Jäger, 2012) comb. nov. (Nepal), B. bomdilaensis (Tikader & Malhotra, 1981) comb. nov. (India), B. indicus (Gravely, 1931) comb. nov. (India), B. cladarus (Jäger, 2012) comb. nov. (Myanmar), B. pingu (Jäger & Minn, 2015) comb. nov. (Myanmar), B. natmataung (Jäger & Minn, 2015) comb. nov. (Myanmar), B. sikkimensis (Gravely, 1931) comb. nov. (India), B. ramosus (Thorell, 1887) comb. nov. (Myanmar), B. goaensis (Bastawade & Borkar, 2008) comb. nov. (India), B. himalayensis (Gravely, 1931) comb. nov. (India), B. meghalayaensis (Tikader, 1976) comb. nov. (India), B. narashinhai (Patel & Reddy, 1988) comb. nov. (India), B. ceylonensis (F.O. Pickard-Cambridge, 1897) comb. nov. (Sri Lanka), B. andamanensis (Gravely, 1931) comb. nov. (Andaman Islands), B. kapuri (Tikader, 1973) comb. nov. (Andaman Islands), B. cochinensis (Gravely, 1931) comb. nov. (India), B. thorelli (F.O. Pickard-Cambridge, 1897) comb. nov. (Sri Lanka), B. lishuqiang (Jäger, 2012) comb. nov. (China: Sichuan), B. banna (Yao & Li in Chu et al. 2022) comb. nov. (China: Yunnan), B. theodorianum (Jäger, 2012) comb. nov. (Thailand, Laos, Vietnam), B. robustus (Thorell, 1897) comb. nov. (Myanmar, Thailand, Laos), B. yaeyamensis (Yoshida, 1998) comb. nov. (Taiwan), B. yulin (Yao & Li in Chu et al. 2022) comb. nov. (China: Yunnan), B. simplex (Thorell, 1897) comb. nov. (Myanmar, Thailand, Laos), B. bayeri (Jäger 2012) comb. nov. (Laos), B. holthoffi (Jäger, 2012) comb. nov. (Laos), B. saci (Ono, 2010) comb. nov. (Vietnam), B. floweri (F.O. Pickard-Cambridge, 1897) comb. nov. (Malaysia Peninsula), B. argentipes (Hasselt, 1893) comb. nov. (Malaysia Peninsula, Singapore, Indonesia: Sumatra), B. palembangensis (Strand, 1906) comb. nov. (Indonesia: Sumatra), B. angigitanus (Roewer, 1938) comb. nov. (Papua New Guinea), B. pulvinatus (Thorell, 1890) comb. nov. (Malaysia: Sarawak), B. hosei (F.O. Pickard-Cambridge, 1897) comb. nov. (Malaysia: Sarawak, Brunei), B. monaghani (Jäger, 2013) comb. nov. (Laos), B. javanus (Pocock, 1897) comb. nov. (Indonesia: Sumatra, Java, Bali), B. fungifer (Thorell, 1890) comb. nov. (Malaysia Peninsula), B. valvularis (Hasselt, 1882) comb. nov. (Indonesia: Sumatra), B. bicostatus (Thorell, 1890) comb. nov. (Malaysia: Sarawak), B. bantaengi (Merian, 1911) comb. nov. (Indonesia: Sulawesi), B. bowonglangi (Merian, 1911) comb. nov. (Indonesia: Sulawesi), B. celebensis (Pocock, 1897) comb. nov. (Indonesia: Sulawesi), B. sagittatus (Giltay, 1935) comb. nov. (Indonesia: Sulawesi), B. kochi (Simon, 1897b) comb. nov. (Indonesia: West Papua), B. sarawakensis (F.O. Pickard-Cambridge, 1897) comb. nov. (Malaysia: Sarawak), B. philippinensis (F.O. Pickard-Cambridge, 1897) comb. nov. (Philippines), B. aruanus (Strand, 1911) comb. nov. (Indonesia: Maluku), B. angularis (Roewer, 1938) comb. nov. (Indonesia: Maluku), B. rufisternis (Pocock, 1898) comb. nov. (Papua New Guinea: New Britain), and B. corniger (F.O. Pickard-Cambridge, 1898) comb. nov. (South Africa). For thirty-two species, illustrations of their respective copulatory organs, as well as habitus photos, are provided. Fifty-five new species are described, these are listed, together with the already described species, according to their geographic occurrence and to their affiliation to species groups as far as the latter could be recognised (type species indicated by an asterisk): Bowie hunkydory spec. nov. (Nepal), B. ziggystardust spec. nov. (Nepal), B. ladystardust spec. nov. (Nepal), B. aladdinsane spec. nov. (India), B. majortom spec. nov. (Nepal), B. jeangenie spec. nov. (India), B. heroes spec. nov. (India), B. fascination spec. nov. (Vietnam), B. low spec. nov. (Thailand), B. dodo spec. nov. (Vietnam), B. stationtostation spec. nov. (Myanmar), B. candidate spec. nov. (Vietnam), B. diamonddogs spec. nov. (Vietnam), B. yassassin spec. nov. (Taiwan), B. bemywife spec. nov. (Thailand), B. subterraneans spec. nov. (Thailand), B. afterall spec. nov. (Thailand), B. warszawa spec. nov. (Thailand), B. artdecade spec. nov. (Cambodia), B. bigbrother spec. nov. (Vietnam), *B. rebelrebel spec. nov. (Vietnam), B. youngamericans spec. nov. (Vietnam), B. right spec. nov. (Vietnam), B. stay spec. nov. (Vietnam), B. fame spec. nov. (Vietnam), B. win spec. nov. (Vietnam), B. joethelion spec. nov. (Malaysia Peninsula), B. mossgarden spec. nov. (Malaysia Peninsula), B. neukoeln spec. nov. (Malaysia Peninsula), B. scarymonsters spec. nov. (Indonesia: Sumatra), B. teenagewildlife spec. nov. (Indonesia: Sumatra), B. letsdance spec. nov. (Indonesia: Java), B. crystaljapan spec. nov. (Indonesia: Sumatra), B. tonight spec. nov. (Malaysia: Sarawak), B. catpeople spec. nov. (Malaysia: Sabah), B. ricochet spec. nov. (Indonesia: Kalimantan), B. fashion spec. nov. (Malaysia Peninsula), B. withinyou spec. nov. (Malaysia: Sarawak), B. abdulmajid spec. nov. (Singapore), B. blackout spec. nov. (Malaysia Peninsula), B. modernlove spec. nov. (Malaysia: Sabah), B. chinagirl spec. nov. (Malaysia: Sabah), B. withoutyou spec. nov. (Malaysia: Sabah), B. magicdance spec. nov. (Indonesia: Sulawesi), B. bluejean spec. nov. (Malaysia: Sabah), B. criminalworld spec. nov. (Malaysia: Sabah), B. shakeit spec. nov. (Malaysia: Sabah), B. ashestoashes spec. nov. (Indonesia: Kalimantan), B. underground spec. nov. (Indonesia: Kalimantan), B. lodger spec. nov. (Philippines), B. redsails spec. nov. (Philippines), B. thenextday spec. nov. (Indonesia: Papua), B. lazarus spec. nov. (Papua New Guinea), B. thiesi spec. nov. (Papua New Guinea) and B. blackstar spec. nov. (Papua New Guinea). Formerly unknown sexes are described for the first time for the following species: Bowie martensi comb. nov. (female), B. indicus comb. nov. (only male RTA tip), B. narashinhai comb. nov. (male), B. argentipes comb. nov. (female) and B. celebensis comb. nov. (male). Fourteen species groups are proposed on the basis of morphological characters: cladarus-species group (17 species), robustus-species group (14 species), bemywife-species group (2 species), rebelrebel-species group (10 species), youngamericans-species group (3 species), floweri-species group (3 species), scarymonsters-species group (2 species), teenagewildlife-species group (2 species), argentipes-species group (10 species), javanus-species group (5 species), chinagirl-species group (11 species), shakeit-species group (5 species), lodger-species group (3 species) and blackstar-species group (7 species). Thus, 93 species are grouped, leaving 11 species without a current assignment to any of these groups. Ctenus kandyensis Kim & Ye, 2014 syn. nov. is recognised as a junior synonym of Bowie thorelli comb. nov., and C. calcarifer F.O. Pickard-Cambridge, 1902 syn. nov. as junior synonym of B. sarawakensis comb. nov. Five species previously placed in Ctenus are considered nomina dubia, four of them are transferred to Bowie gen. nov., one to Nilus: Bowie barbatus (Thorell, 1895) comb. nov., B. tumidulus (Simon, 1887b) comb. nov., B. flavidus (Hogg, 1922) comb. nov., B. pollii (Hasselt, 1893) comb. nov. and Nilus marginatus (Walckenaer, 1847) comb. nov. Beside the latter species, three species are transferred from Ctenus, all of them to Anahita: A. periculosa (Bristowe, 1931) comb. nov., A. dangsa (Reddy & Patel, 1994) comb. nov. and A. tuniensis (Patel & Reddy, 1988) comb. nov. All in all, Bowie gen. nov. is the second largest genus within the family Ctenidae, with 108 species in total including nomina dubia. It occurs from Nepal in the Himalayas and South India across large parts of South and South East Asia to Papua New Guinea. One undescribed species is known from northern Australia (Queensland). Representatives are known to live in the leaf litter of forests, with most species having small distribution ranges, usually occurring within a 100 km radius. With this revision, the family Ctenidae contains now 586 species and 48 genera, and the number of species assigned to the genus Ctenus, so far used as nomenclatural “waste bin”, is reduced to 164.